Economic Growth And Carbon Emission: A Dynamic Panel Data Analysis - BAKIRTAS, Ibrahim; BAYRAK, Seyhat; CETIN, Atalay (European Journal of Sustainable Development, 2014)
The relationship between carbon dioxide emission (CO2) and economic growth is one of the crucial topics in environmental economics. This study is aimed to investigate that problem. In this study, depending on the theory of Environmental Kuznets Curves (EKC), the impact of income in carbon dioxide emission has measured for 34 OECD and 5 BRICS countries with using Dynamic Panel Data Analysis. In this regard OECD countries are classified by income groups due to the average per capita income rate of OECD to solve the homogeneity problem among OECD countries. On the other hand EKC hypothesis analysed by short and long run income elasticity which will be using for an evident that a country reduces CO2 emissions with the income increase in this study. According to the findings of the study, % 36 of the country sample coherent with the EKC hypothesis. The main encouragement for testing this relationship between economic growth and CO2 emission is leading politicians to reconsider the environmental impacts which are arising from income increase when they are taking a decision to maximizes the economic growth. Keywords: EKC; OECD; Dynamic Panel Data